2023
DOI: 10.4236/as.2023.141004
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potential of Cowpea-Wheat Double Cropping in the Semi-Arid Region of the Southern United States Using the DSSAT Crop Model

Abstract: Information is limited on the potential of double-cropping cowpea (Vigna unguiculata L.) and wheat (Triticum aestivum L.) in the semiarid region of the southern United States. Using the Decision Support System for Agrotechnology Transfer (DSSAT) crop model and weather data of 80 years, we assessed the possibility of cowpea-wheat double-cropping in this region for grain purpose as affected by planting date and N application rate. Results showed that the possibility of double-cropping varied from 0% to 65%, depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…For the scenarios comprising wheat planted before October 15 or October 30 following cowpea planted in June or July, respectively, either the ENSO comparison was not possible because of no feasibility of cowpea-wheat doubling cropping in the study region [70], or, in the cases of feasible scenarios, the d wheat yields were not significantly different across ENSO phases. With a long-term simulation study conducted for the Llano Estacado region using 80 years' weather data, reference [70] found that the number of feasible years for cowpea-wheat double-cropping in the Llano Estacado region ranged from 0 to 52, depending on the double-cropping scenario comprising the planting dates of cowpea and wheat (Figure 8). As they demonstrated, the feasibility was highest, about 65%, with July 15 and November 30 as the planting dates of cowpea and wheat, respectively.…”
Section: The Enso Effect On Double-cropped Wheat Yieldsmentioning
confidence: 99%
“…For the scenarios comprising wheat planted before October 15 or October 30 following cowpea planted in June or July, respectively, either the ENSO comparison was not possible because of no feasibility of cowpea-wheat doubling cropping in the study region [70], or, in the cases of feasible scenarios, the d wheat yields were not significantly different across ENSO phases. With a long-term simulation study conducted for the Llano Estacado region using 80 years' weather data, reference [70] found that the number of feasible years for cowpea-wheat double-cropping in the Llano Estacado region ranged from 0 to 52, depending on the double-cropping scenario comprising the planting dates of cowpea and wheat (Figure 8). As they demonstrated, the feasibility was highest, about 65%, with July 15 and November 30 as the planting dates of cowpea and wheat, respectively.…”
Section: The Enso Effect On Double-cropped Wheat Yieldsmentioning
confidence: 99%